Peningkatan Kemampuan Kognitif Anak Kelompok B Melalui Metode Proyek - Dahlia Ismail; Mulyadi Mulyadi; Nirwana Nirwana (PG PAUD Universitas Islam Makassar | LP2M-UIM | PPJ PAUD (Perhimpunan Pengelola Jurnal PAUD) Indonesia, 2025)
This study aims to improve early childhood cognitive abilities through the implementation of the project-based learning method in Group B at Annur Buloa Kindergarten, Makassar City. The background of the study is driven by the low skills of children in arranging, grouping, and ordering objects due to the dominance of passive, conventional learning methods. Cognitive ability is a crucial foundation for children's academic readiness; therefore, pedagogical innovations capable of optimally stimulating executive functions are urgently required. The research method employed is collaborative Classroom Action Research (CAR) conducted in two cycles. The research subjects consisted of 15 children who were observed through data collection techniques including participatory observation, interviews, and documentation. Data analysis was performed qualitatively and through descriptive quantitative measures to examine developmental trends in each cycle. The results demonstrate that the implementation of the project method significantly transforms children's cognitive abilities. Substantively, this change is characterized by an increase in children's independence in solving logical problems and accuracy in classifying objects using concrete media. The findings reveal that by the final cycle, the majority of children achieved the highly well-developed category, surpassing the predetermined success indicators. This study concludes that the project method is effective in enhancing cognitive abilities as it provides opportunities for children to become protagonists in their learning through exploration, inquiry, and collaboration. The teacher's role as a facilitator who provides adaptive guidance serves as the key factor in the success of this method. The implications of this study emphasize the importance of early childhood educators shifting from one-way instruction to more meaningful and contextual project-based learning strategies.